The criterion problem in cross-cultural performance research. (December 2022) - Kell, Harrison J
The criterion problem is a serious conceptual and methodological challenge that has confronted investigators and managers in the organizational sciences for over 100 years. This paper is an introduction to the criterion problem and some of the complex, multifaceted issues it encompasses. It defines and discusses important concepts (e.g. the problem itself, conceptual criteria, operational criteria). It explores broad dilemmas that afflict all types of criteria and narrower dilemmas that are more individually relevant to criteria traditionally considered objective or subjective. It concludes by examining prospects for the criterion problem both in general and within cross-cultural management.